Diagnostic delay in a French cohort of Crohn's disease patients. (1st September 2014) - Nahon, Stéphane; Lahmek, Pierre; Lesgourgues, Bruno; Poupardin, Cécile; Chaussade, Stanislas; Peyrin-Biroulet, Laurent; Abitbol, Vered
Abstract: Diagnostic delay is frequent in Crohn's disease (CD) and may partly depend on socioeconomic status. The aim of this study was to determine the diagnostic delay and to identify associated risk factors, including socioeconomic deprivation in a French cohort of CD patients. Methods: Medical and socioeconomic characteristics of all consecutive CD patients followed in 2 referral centers between September 2002 and July 2012 were prospectively recorded using an electronic database. Diagnostic delay was defined as the time period (months) from the first symptom onset to CD diagnosis. A long diagnostic delay was defined by the upper quartile of this time period. Univariate and multivariate analyses were performed to identify the baseline characteristics of patients associated with a long diagnostic delay. Results: Three hundred and sixty-four patients with CD (mean age = 29.2 ± 12.6 years, 40.8% men) were analyzed. Median diagnostic delay was 5 months, and a long diagnostic delay was more than 12 months. Fifty-six patients (15.3%) had perianal lesions, and 28 patients (8.6%) had complicated disease at diagnosis. None of the following factors were associated with a long diagnostic delay: age, gender, CD location and behavior, marital and educational, language understanding, geographic origin and socioeconomic deprivation score measured by the EPICES score. Conclusion: In this French referral center-based cohort of CD patients, the median diagnostic delay was 5 months. None of the baseline characteristics of the CD, including socioeconomic deprivation, influenced diagnostic delay in this cohort.